PROPUESTA DE UN MODELO EMPÍRICO PARA EVALUAR LA CALIDAD DE LA EDUCACIÓN SUPERIOR A DISTANCIA EN MÉXICO - Aguilar, Alma Lilia Sapién; Howlet, Laura Piñón; Gutiérrez Diez, María Del Carmen (European Scientific Journal, ESJ, 2013)
The objective was to design and propose a Quality Evaluation Model in the distance mode (MECMD). The MECMD was based on criteria, sub-criteria, requirements and means of verification, and five fundamentals were taken as a base; pertinence, equity, efficiency, effectiveness and, internationalization. The results showed that in Mexico 70% of the higher education institutions are public and all of them accredited in the presential modality, so there is a lack of assessment models and certification for unconventional programs. The 10 criteria on which this model was based are; leadership, planning, institution, study plan, management of information, knowledge, technology and innovation, professors, staff, students, extension and research, and results.